Selective interfacial synthesis of metal-organic frameworks on a polybenzimidazole hollow fiber membrane for gas separation - Biswal, Bishnu P.; Bhaskar, Anand; Banerjee, Rahul; Kharul, Ulhas K. (Nanoscale, 2015)
Metal-organic frameworks (MOFs) have gained immense attention as new age materials due to their tuneable properties and diverse applicability. However, efforts on developing promising materials for membrane based gas separation, and control over the crystal growth positions on polymeric hollow fiber membranes still remain key challenges. In this investigation, a new, convenient and scalable room temperature interfacial method for growing MOFs (ZIF-8 and CuBTC) on either the outer or inner side of a polybenzimidazole based hollow fiber (PBI-BuI-HF) membrane surface has been achieved in a controlled manner. This was made possible by the appropriate selection of an immiscible solvent pair and the synthetic conditions. The growth of MOFs on the PBI-BuI-HF membrane by the interfacial method was continuous and showed an appreciable gas separation performance, conveying promise for their applicability.